Evaporation dynamics of water droplets on superhydrophobic nanograss surfaces. (October 2020) - Aldhaleai, Ahmed; Khan, Faheem; Thundat, Thomas; Tsai, Peichun Amy
Highlights: Wetting of evaporating drops on superhydrophobic Nanograss surfaces is elucidated. Sharp nanograss greatly increases the duration of gas-trapping state with a CCA mode. Small droplets evaporate with a CCA mode, followed by a mixed mode. Large droplets exhibit intriguing stick-slip motions of the contact line. Evaporative cooling model predicts the evaporation rate on the SH nanograss well. Graphical abstract: Abstract: Evaporation of a sessile droplet on superhydrophobic surfaces has various applications due to their utmost water-repellent and self-cleaning wetting properties. We experimentally investigate the evaporation dynamics of water droplets and the time evolution of the contact angle and drop dimensions on superhydrophobic, nanograss substrates of an extremely-low solid packing fraction ( ϕ  ≈ 0.005). The experimental data shows that all the droplets deposited initially form a gas-trapping, Cassie-Baxter state. Small droplets subsequently evaporate with a constant contact angle mode, followed by a mixed mode at the end of the droplet lifetime. On the contrary, for relatively large droplets, two distinct evaporation modes are found. Some of the larger evaporating droplets were initially in a constant contact angle mode and underwent a mixed mode, while others began with a mixed mode with slowly decreasing base diameter and contact angle. Intriguingly, stick-slip motions of the contact line for large droplets are observed using superhydrophobic nanograss surfaces. Such slip or jumping motion could be related to the excess free energy available in the system when the receding contact angle is reached, resulting in the contact line movement. Finally, the experimental data of contact angle dependent evaporative mass flux are found to nearly collapse onto one universal curve for different droplet sizes and initial contact angles, in agreement with an evaporative cooling model.